Tourism and Its Impact on the Local Economy of Nagarkot - Rai, Sumita (Nepal Tourism and Development Review, 2013)
Nagarkot is a popular holiday destination 32 km north-east from the capital city, Kathmandu. It is situated at the altitude of 7, 200 feet. The place is known specifically for its dawn time, for a beautiful view of sunrise over the Eastern Himalayas. The best time to visit Nagarkot would be between October and March. Monsoon clouds obstruct wonderful views between June and September. Nagarkot is very much a resort village, where people come to escape the sweltering heat of the city and stay overnight. Very few visitors stay longer. This article, using field-notes, briefly describes the status of tourism at Nagarkot. The study takes the case of four major aspects of tourism industry – accommodations, restaurants, tourists and outlets – to examine the impact of tourism in the local economy. DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7385 Nepal Tourism and Development Review Vol.2(1) 2012 155-159